2002
DOI: 10.1614/0890-037x(2002)016[0414:eopara]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Postemergence Application Rate and Timing of Mesotrione on Corn (Zea mays) Response and Weed Control1

Abstract: Field experiments were conducted in 1999 and 2000 to determine the influence of mesotrione postemergence application rate, application timing, and addition of atrazine on corn injury, weed control, and corn grain yield. Corn injury in the form of leaf bleaching ranged from 0 to 15% at 7 d after treatment (DAT). In general, most of the bleaching injury rapidly dissipated with slight (≤ 8%) to no corn injury observed at 28 DAT. Control of common cocklebur with mesotrione at 14 DAT ranged from 79 to 98% for all t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
61
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 8 publications
(8 reference statements)
6
61
1
1
Order By: Relevance
“…In addition, the rates required to achieve an acceptable response i.e., control and percent shoot biomass reduction varied between weed species (Tables 1 and 2). Johnson et al (2002) reported variable control of common cocklebur (Xanthium strumarium L.), ivyleaf morning glory (Ipomoea hederacea L.), and yellow nutsedge (Cyperus esculentus L.) following POST application of mesotrione; however, response was improved by increasing application rates.…”
Section: Kochiamentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the rates required to achieve an acceptable response i.e., control and percent shoot biomass reduction varied between weed species (Tables 1 and 2). Johnson et al (2002) reported variable control of common cocklebur (Xanthium strumarium L.), ivyleaf morning glory (Ipomoea hederacea L.), and yellow nutsedge (Cyperus esculentus L.) following POST application of mesotrione; however, response was improved by increasing application rates.…”
Section: Kochiamentioning
confidence: 99%
“…The efficacy of herbicides is influenced by several factors including type of weed species present, growth stage, and herbicide application rates (King and Oliver 1992;Jordan et al 1993;Johnson 2002;Abendroth et al 2006). However, the use of herbicides at the labeled rate and appropriate crop and weed stages usually results in high weed mortality and crop safety.…”
mentioning
confidence: 99%
“…Curran et al (1991) reported that clomazone, chlorimuron, and imazaquin applied to V3 corn caused significant injury (up to 39% chlorosis) but did not affect corn yield. Similarly, Johnson et al (2002) observed foliar injury from the herbicide mesotrione applied to V3 to V5 corn but did not observe any yield differences between herbicide-treated and nontreated corn. Corn appears to be tolerant to injury during early-vegetative growth, indicating that the lack of grain yield response to foliar Zn injury is not unusual.…”
Section: Resultsmentioning
confidence: 79%
“…The mesotrione inhibit carotenoid biosynthesis, interfering with the activities of the enzyme HPPD (4-Hydroxyphenylpyruvate dioxygenase) in the chloroplasts, causing bleaching with subsequent necrosis and plant tissues death in about one or two weeks (Mitchell et al, 2001). Johnson, Young, & Matthews (2002) observed injuries to the maize plants seven days after the application of mesotrione, depending on the season and the dose applied.…”
Section: Resultsmentioning
confidence: 99%